THE EFFECT OF FLIPPED CLASSROOM METHOD ON THE STUDENTS’ READING HORTATORY EXPOSITION TEXT FOR IX GRADE SMP SWASTA MADANI MARINDAL -I: PENGARUH METODE FLIPPED CLASSROOM TERHADAP PEMBACAAN TEKS HORTATORY EKSPOSISI SISWA KELAS IX SMP SWASTA MADANI MARINDAL -I - Laia, Rianghati (LPPM UPMI, 2024)
The effect of the flipped class method on students reading hortatory exposition texts in class IX of SMPS Madani Marindal – I. A thesis. English Language Education, Faculty of Teacher Training and Education, Indonesian Community Development University. Supervisor: (I) Fatin Nadifa Br Tarigan, S.Pd., M.Hum. (II) Nurmayana, S.Pd., M.Li. Helping students to reading English is a problem that must be solved. So this is the background for carrying out this research. The aim of this research is to determine the effect of using the flipped class method in students' reading learning and to find out whether students are interested in learning with this method. The subjects in this research were class IX students at SMPS Madani Marindal – I Medan for the 2023/2024 academic year, totaling 65 students. This research uses one class, namely class IX. In this study, researchers applied an experimental research design involving pre-test and post-test to measure student achievement in reading hortatory exposition. Researchers used one instrument. There are tests carried out, including pre-test and post-test. Based on the results of data processing, the results showed that there was a significant increase, namely the average post-test score was higher than that found in the pre-test (68.8>48.52) and (82.29>49.51). From the results of the changed data, it can be concluded that students have experienced improvements in learning by using the flipped class. And the results of interviews conducted with English teachers prove that this method is effective for students. The research hypothesis in this study shows the number 7.32. And this is included in the good category and it can be said that this research is valid and significant.